The Contribution of Tax Incentives during Core Tax Administration System to Enhance ESG Performance in Indonesia - Indriastuti, Mila; Ardin, Galih (Politeknik Keuangan Negara STAN, 2024)
The application of Environmental, Social, and Governance (ESG) principles is increasingly becoming a global concern as an indicator of corporate sustainability. However, in Indonesia, tangible support from the government in the form of fiscal incentives for companies with good ESG performance is still limited. This study aims to examine the tax incentive policies that apply during the implementation of the core tax administration system (CTAS) to companies that have good ESG performance. The research method used is qualitative with a narrative approach, where data is obtained through interviews with competent informant in the field of taxation and ESG. The results show that during the CTAS implementation period, the Indonesian government has not fully provided specific tax incentives for companies with superior ESG performance. This indicates the need for tax policy reformulation in order to encourage sustainable business practices through more targeted incentives.